PERAN PENDIDIKAN ISLAM DALAM MENINGKATKAN KETAHANAN KELUARGA DI ERA TEKNOLOGI DAN MODERN - Khasnah Syaidah; Siti Rohmah; Siti Sarah Zakiyah (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2025)
In the modern technological era, family resilience faces complex challenges. Islamic education plays a crucial role in strengthening family bonds with solid values. Wise utilization of technology enables Islamic education to adapt to the evolving times, maintain relevance, and enhance family resilience in navigating global dynamics. This study describes the role of Islamic education in improving family resilience in the modern technological era through relevant strategies and implementations. The research method used is descriptive analysis with a literature review, referring to written sources such as books, encyclopedias, and scientific journals. The data is coded, analyzed categorically, and structured into a logical, systematic, and reflective narrative.  The findings indicate that Islamic education is essential in instilling moral values, guiding families in overcoming technological challenges, and managing stress through spiritual practices and a holistic approach. Furthermore, Islamic education supports the balance between career and personal life, strengthens economic stability through skill development, and fosters solidarity within the community. The implementation of Islamic values in strengthening family resilience includes character development based on noble ethics, effective communication, clear role distribution, spirituality cultivation, health education, and socio-economic skill development. Values such as honesty, empathy, compassion, and trustworthiness help families navigate modern challenges with harmony, tranquility, and resilience. Through this approach, families become more robust and adaptive to the changing times.